Makna Frasa Berturut-Turut dalam Pasal 19 Ayat (3) Undang-Undang Jabatan Notaris - Ni Made Dwita Andayana Dewi; I Wayan Novy Purwanto (Jurnal Interpretasi Hukum, 2025)
The clarity of meaning in every provision of the law is essential to prevent differences in interpretation that may hinder the realization of legal certainty and justice in its aplication. This research intends to evaluate the juridical implications of successive Notarial instrument executed outside from the notary's residence with regard to their legality and to interpret the phrases "consecutively" under Article 19 paragraph (3) in the UUJN. The UUJN ambiguous norm is the source of this study. The study adopts a normative legal research method, With reference to both main and supporting souces of law. The analysis applies conceptual and legislative approaches as the methods of analysis. Data collection techniques include document studies and qualitative studies, intended to gather naturalistic data consisting of textual information. Based on the results obtained, it can be inferred that the phrase “consecutively” in the UUJN is interpreted as a prohibition for notaries to continuously perform their official duties outside their domicile without a reasonable interval and without legitimate reasons as referred to in the specific grounds provided under Article 3 point 15 of the KEN. This phrase serves as a limitation to ensure that the exercise of notarial duties remains within the boundaries of professionalism, ethics, legal certainty, and justice. The execution of a notarial deed outside the notary’s domicile, whether or not based on “certain reasons,” is allowed provided that it is still within the notary’s official jurisdiction and in accordance with Article 19(3) in the UUJN.